Cilioretinal artery hypoperfusion and its association with paracentral acute middle maculopathy. Issue 8 (26th September 2018) - Pichi, Francesco; Fragiotta, Serena; Freund, K Bailey; Au, Adrian; Lembo, Andrea; Nucci, Paolo; Sebastiani, Stefano; Gutierrez Hernandez, Juan Carlos; Interlandi, Emanuela; Pellegrini, Francesco; Dolz-Marco, Rosa; Gallego-Pinazo, Roberto; et al.
Abstract : Background/aims: To study the multimodal imaging findings of a large series of eyes with cilioretinal artery obstruction (CILRAO) and describe the systemic associations. Methods: Multicentre, retrospective chart review from 12 different retina clinics worldwide of eyes with CILRAO, defined as acute retinal whitening in the distribution of the cilioretinal artery, were identified. The clinical, systemic information and multimodal retinal imaging findings were collected and analysed. Results: A total of 53 eyes of 53 patients with CILRAO were included in the study. In 100% of eyes, fundus photography illustrated deep retinal whitening corresponding to the course of the cilioretinal artery. Twenty-eight patients (52.8%) presented with isolated CILRAO (baseline best-corrected visual acuity (BCVA) 20/50, final BCVA 20/25) associated with nocturnal hypotension, 23 patients (43.4%) with CILRAO secondary to central retinal vein occlusion (CRVO) (baseline BCVA 20/40, final BCVA 20/20) and two patients with CILRAO due to biopsy-proven giant cell arteritis (GCA) (baseline BCVA 20/175, final BCVA 20/75). With spectral domain optical coherence tomography (SD-OCT), a hyper-reflective band involving the inner nuclear layer (ie, paracentral acute middle maculopathy or PAMM) was noted in 51 eyes (28/28 eyes with isolated CILRAO and 23/23 eyes with CILRAO+CRVO) corresponding to the retinal whitening. In the two eyes with CILRAO+GCA, SD-OCT illustrated hyper-reflective ischaemia of both the middle and inner retina. Conclusions: Isolated CILRAO and CILRAO secondary to CRVO are the result of hypoperfusion or insufficiency, rather than occlusion, of the cilioretinal artery and are associated with PAMM or selective infarction of the the inner nuclear layer. With GCA, there is complete occlusion of the cilioretinal artery producing ischaemia involving both the middle and inner retina associated with worse visual outcomes.